Policy Analysis of Tobacco Excise Sharing Fund (Roccipi Method) - Nugroho, Ramadhany; Setijaningrum, Erna (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
Indonesia ranks fourth in the world in tobacco production, with an annual production of 237.11 thousand metric tons. With an approximate number of 84.35 million, Indonesia claims the third rank of largest number of smoking individuals in the world. In 2022, the government's revenue from tobacco excise reached IDR 218.64 trillion, with an increase in revenue target of IDR 245.4 trillion in 2023. The government aims to channel these excise revenues back to society for development and addressing the externalities caused by tobacco consumption. To achieve this goal, the government established the Tobacco Excise Revenue Sharing Fund (DBH CHT). However, this earmarking policy has not yielded optimal results, as several externalities related to tobacco consumption remain unaddressed. Considering these challenges, this study aims to (1) identify the national policy, (2) review the content of related legislative regulations, and (3) analyze policy implementation using the ROCCIPI method. The research employs a qualitative approach, drawing from observations, semi-structured interviews, and previous studies. Based on the ROCCIPI analysis, the study suggests the need for adjustments in the content of DBH CHT legislative regulations, particularly regarding the budget allocation formula. Additionally, it highlights the absence of derivative regulations from relevant technical ministries, potential budget misappropriation, limited understanding of legislative regulations, budget absorption difficulties, and insufficient regulation awareness campaigns.